The Corporate Propensity to Save - RIDDICK, LEIGH A.; WHITED, TONI M. (Journal of Finance, 2009)
Why do corporations accumulate liquid assets? We show theoretically that intertemporal trade-offs between interest income taxation and the cost of external finance determine optimal savings. Intriguingly, we find that, controlling for Tobin's q, saving and cash flow are negatively related because firms lower cash reserves to invest after receiving positive cash-flow shocks, and vice versa. Consistent with theory, we estimate negative propensities to save out of cash flow. We also find that income uncertainty affects saving more than do external finance constraints. Therefore, contrary to previous evidence, saving propensities reflect too many forces to be used to measure external finance constraints.